2013
DOI: 10.1177/0957650913498081
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance calculations of chemically recuperated gas turbine on ship

Abstract: This paper describes the design and performance analysis of a chemically recuperated gas turbine powering a ship. The system studied consisted of an efficient steam-generating system, a reforming regenerator, and a gas turbine. Mathematical models were built for the performance analyses. An efficient steam-generating system was designed and the effects of various parameters on the steam generation were studied. The calculations indicate that the steam-generating system can meet the steam requirements for refor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The efficiency of the gas turbine power module with a thermochemical natural gas treatment system with a thermochemical reactor behind a power turbine obtained by mathematical modelling methods shows that, at the relatively low levels of gas temperatures behind the combustion chamber (<1523 K) and the exhaust gases (700-820 К), steam conversion of natural gas due to the heat of exhaust gases is not efficient enough and can be compared with the STIG cycle. This coincides with the results of other researchers [27].…”
Section: Fig 5 Dependence Of Efficiency Increase On the Temperature B...supporting
confidence: 94%
“…The efficiency of the gas turbine power module with a thermochemical natural gas treatment system with a thermochemical reactor behind a power turbine obtained by mathematical modelling methods shows that, at the relatively low levels of gas temperatures behind the combustion chamber (<1523 K) and the exhaust gases (700-820 К), steam conversion of natural gas due to the heat of exhaust gases is not efficient enough and can be compared with the STIG cycle. This coincides with the results of other researchers [27].…”
Section: Fig 5 Dependence Of Efficiency Increase On the Temperature B...supporting
confidence: 94%
“…As a result, engine power and efficiency improve. Pan et al have found that the chemically recuperated gas turbine engine (where waste heat is used for steam fuel reforming) improved combustion and achieved higher thermal efficiency [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A chemically recuperated marine gas turbine was studied by Pan et al [43]. They applied mathematical models for performance analysis.…”
Section: Introductionmentioning
confidence: 99%